2020
DOI: 10.3390/pharmaceutics12010060
|View full text |Cite
|
Sign up to set email alerts
|

Zein Beta-Cyclodextrin Micropowders for Iron Bisglycinate Delivery

Abstract: Given the limited number of materials available to design delivery platforms for nutrients, the rational combination of raw materials already approved as food ingredients and their processing through nano-micro technology can offer a unique tool for innovation. Here, we propose a nano-in-micro strategy to produce powders based on the hydrophobic protein zein, useful for the oral delivery of a hydrophilic iron source (iron bisglycinate) in anaemic patients. Iron-loaded powders were prepared through a two-step s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Peaks ranging from to 1645 cm −1 were due to the stretching vibration of C=O(-CH2-CO-CH2-) and the ben ring [46]. The results listed several peaks at respective wavenumbers (cm −1 ) including tributions from various functional groups of Zein at 2974.87, 2872.89, and 1421.51 [47][48][49][50][51]. Results indicated that capsaicin and Zein had been functionalized successf Embedding essential oils (EOs) into MSNs makes it possible to slow down the release where encapsulation and covalency are essentially two forms of EOs' insertion.…”
Section: Fourier Transform Infrared Spectroscopy (Ftir)mentioning
confidence: 96%
“…Peaks ranging from to 1645 cm −1 were due to the stretching vibration of C=O(-CH2-CO-CH2-) and the ben ring [46]. The results listed several peaks at respective wavenumbers (cm −1 ) including tributions from various functional groups of Zein at 2974.87, 2872.89, and 1421.51 [47][48][49][50][51]. Results indicated that capsaicin and Zein had been functionalized successf Embedding essential oils (EOs) into MSNs makes it possible to slow down the release where encapsulation and covalency are essentially two forms of EOs' insertion.…”
Section: Fourier Transform Infrared Spectroscopy (Ftir)mentioning
confidence: 96%
“…32 The number of studies on the application of cyclodextrins for iron delivery is scarce in the literature. Esposito and coworkers 33 investigated the application of pseudolatex prepared using zein and βCD combined with spray drying for the delivery of iron bisglycinate. Delivery of ferrous fumarate by βCD and 2-hydroxypropyl-β-cyclodextrin (HP-βCD) is also reported by Kapor et al 34 Water-soluble iron sources that can be used for food fortification include ferrous sulphate, ferrous gluconate, ferrous lactate, ferric ammonium citrate, ferrous bisglycinate, and ferric sodium EDTA.…”
Section: Application Of Cyclodextrins For Iron Deliverymentioning
confidence: 99%